Лідерські якості спортсменів як складова їх готовності до професійного самовизначення після завершення спортивної кар'єри - Тіняков, Артем Олександрович; Арабаджи, Тимур Дмитрович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто проблему лідерства у спорті та питання розвитку лідерських якостей і рис особистості, які мають позитивно реалізовуватися у подальшій професійній кар‟єрі людини по завершенню спортивної кар'єри. Визначено, що одним з пріоритетних завдань виховної роботи зі спортсменами є формування і розвиток у них лідерських якостей. У зв'язку з цим особливу важливість набуває необхідність здійснення відповідної діагностики лідерського потенціалу спортсменів і його своєчасне виявлення. В результаті діагностування особистісних якостей студентів-спортсменів виявлено лідерські якості, які студенти-спортсмени високо оцінюють та водночас визначають властивими для себе, а також лідерські якості, що студенти-спортсмени вважають найменш розвиненими у себе, але значущими і важливими у подальшій професійній кар‟єрі.

Problem setting. The article deals with the problems of leadership in sports and the formation of leadership qualities of athletes as an important component of their readiness for professional self-determination after the end of а sports careers. The problem of development of leadership qualities during sports is considered by scientists in various aspects of psychological and pedagogical researches from the standpoint of education of volitional qualities, and the positive influence of physical education, fitness and sports on the formation of leadership qualities is explored in the context of spiritual development of the individual. The problem of leadership in sports is also one of the most important in sports psychology. Leadership in sports is considered mainly from the point of view of dynamics of interpersonal relations in sports teams and groups (teams) and / or activity of the trainer as a leader. Recent research and publications analysis. According to many psychologists, the effectiveness of leadership in sports depends on the combination or interaction of situational factors and leadership behavior. The formation of leadership qualities of athletes is also considered by psychologists as a result of internal group processes in the sports environment, such as the influence of leadership on team cohesion, the formation of psychological climate and the system of relationships between members of the sports team, the balance of rivalry (competition) and cohesion in the sports team for students, the ratio of formal and informal leadership in the sports team. Despite significant improvements, the unresolved part of the problem remains the formation of leadership qualities and personality traits in sports, which should be positively pursued in the further professional activity after the end of his sports career. Paper main body. The current concept of educational work in the children and youth sports requires a more meaningful approach to the problem of developing the leadership potential of athletes. In our opinion, the priority of educational work with student-athletes is the formation and development of leadership qualities. In this regard, it is important to make an appropriate diagnosis of the leadership qualities of athletes and their timely detection. Athletes devote many years to sports improvement. A key condition for the development of leadership qualities is the process of self-realization of inner potential, which contributes to the constant desire and motivation to achieve high sports results in childhood, adolescence and youth. The central factor in this process is the phenomenon of "internal leadership", that is, a state of personality based on constant, regular self-organization and the desire for continuous sports development and improvement. Athletes develop specific personality traits, among which many researchers highlight leadership qualities such as commitment, courage, self-regulation, stress, competitiveness, vigor, dominance, and others that are the key to achieving sports results. Sports activities are characterized by a practical focus on the acquisition of specific organizational skills. The development of leadership qualities of athletes occurs through the development of specific organizational skills in the process of engaging in joint constructive interaction, an example of which is a coordinated teamwork. In the process of sports activities, the inner content of the personality, his potential and ability to work on himself are revealed. This is achieved by development of physical and psychological abilities; actualization of personally meaningful activity and desire to achieve results; promoting the development of a strategy of successful personality through sports achievements. According to the results of modern research, leadership potential is in everyone and is amenable to development. The discovery of leaders and the self-realization of athletes occurs not only in sports, but also in activities that are in one way or another connected with sports: during a regulated training process and participation in competitions, during participation in camps, clinics, specialized trainings, as well as in the process of independent acquisition of professional and specialized knowledge and skills. For purposeful development of leadership qualities during sports training of the trainer it is necessary to carry out systematic pedagogical monitoring of dynamics of leadership development; to develop and implement programs of socially significant activity; interact with social institutions; coordinate the activities of youth organizations in providing methodological, informational and legal assistance to athletes. The study found that most student-athletes understand the concept of "leader" as the ability to effectively influence others, mobilize the team and manage it to achieve results. Most respondents understand the role of a leader from a humanistic standpoint as a person committed to supporting friendly and constructive team relationships. Important is the perception of the team leader as a person who is able to maximize his or her own abilities for success in training and sports. According to the respondents, the leader's activity should be different for active participation in the life of the team, organization, club, work of various public associations and more. According to student-athletes, sports should promote those leadership qualities that will contribute to the success of future professional activity after completing a sports career. Student-athletes highly value and at the same time determine their own leadership qualities such as organizational skills, ability to work in a team, friendliness, ability to manage themselves. On the other hand, students with the least developed in themselves, but significant and important leadership qualities, determined their readiness to work as a team and to evaluate events "through the eyes of partners"; the ability to be a partner who does not point but lead; ability to solve problems; to influence others; the ability to trust partners and celebrate their best qualities; the ability to clearly understand one's purpose. The students noted a rather low level of knowledge and skills in organizational work, while considering them as important leadership traits that need to be developed. This will help you to be successful both on the playground and in your future professional activities. Conclusions of the research. The above conclusions do not exhaust the full diversity of leadership qualities and attributes of student-athletes, but merely create a basis for further discussion of the issues raised. Among the promising directions in the organization of scientific research, it is necessary to pay attention, first of all, to the analysis of the content of leadership qualities, which are effectively formed during physical training and sports and to create appropriate psychological and pedagogical conditions.
Leadership qualities of sportsmen as a component of their readiness for professional self-determination after the end of a sports career
Keywords: спорт; спортивне середовище; формування лідерських якостей; sport; sports environment; leadership